PENGARUH TRANSFER PRICING, CAPITAL INTENSITY DAN TAX HAVEN UTILIZATION SEBAGAI UPAYA TAX AVOIDANCE - Tharique Nazhief (2022)
This study aims to determine the effect of transfer pricing, capital intensity, and tax haven utilization on tax avoidance in the non-cyclicals consumer sector for the 2017-2020 accounting period. This research is a quantitative research that uses secondary data in the form of financial reports obtained from the official website of the Indonesia Stock Exchange (IDX) and the company's official website. This study used a sample of 41 companies and 164 total research datas. The technique for analyzing the data in this study uses panel data regression test and partial statistical test (t test) using the STATA 16 application and by the assistance of Microsoft Excel. Based on the results of the tests that have been carried out, it shows that transfer pricing, capital intensity and tax haven utilization do not have a significant effect on tax avoidance. The mean value of the tax avoidance variable obtained is -0.0174, indicating that the average sample company in this study does not do tax avoidance.